The Effect of Perceived Organizational Support, Job Stress, and Organizational Culture on Job Performance - Hafidhah, Rizqi Nur; Martono, S (Universitas Negeri Semarang, 2019)
Performance is an important thing that can support organizational life. With good performance it will certainly make it easier for the organization to achieve its goals. The purpose of this study was to determine the effect of perceived organizational support, work stress, and organizational culture on job performance with partially and simultaneously test. The population in this study were all employees of PDAM Tirta Moedal Semarang City and total of the employess are 482. The samples used in this study were 83 employees using proportional random sampling technique. The methods of data collection are using interviews and questionnaires. The methods of data analysis are instrument feasibility test, descriptive analysis, classic assumption test, multiple regression test, partial significance test (t test), simultaneous significance test (f test), and coefficient of determination test using SPSS program. The results of this study showed that there was positif and significant effect of perceived organizational support and organizational culture on performance. As well as there was negatif and significant effect of job stress on performance. And the results also showed that there is a simultaneous effect independent variables on dependent variable. The conclusion of this study is to increasing employee performance are employees must have a high level of perceived organizational support, good organizational culture, and low job stress levels